SSTS/BRASS General Discussion Group ALA Annual Conference, June 16, 2002. - Bryna R. Coonin (Issues in Science and Technology Librarianship)
The article provides a summary of the STS/BRASS General Discussion Group at the ALA Annual Conference, June 16, 2002.